Special interest groups and 4th best transport pricing - Bernhard Wieland (Technische Universität Dresden, Fakultät Verkehrswissenschaften, 2006)
This paper is organized as follows. In order to explain the basic idea of 4th best pricing more fully the following Section 2 will sketch and discuss the above mentioned Laffont model, where it is shown that under certain conditions a uniform tariff may be preferable to an optional tariff because such a uniform tariff is less amenable to the influence of interest groups. Section 3 will illustrate Laffont?s insight with several examples from the transport sector. Section 4 will conclude.
Keywords: 330